ISLAMIZATION OF KNOWLEDGE: Towards The Revival of Islamic Civilization - Ustadiyah . (TAWASUT, 2022)
Abstract The development and advancement of science and technology gave rise to modern civilization that provided benefits and conveniences for humans, but in reality, it had negative implications for the current global humanitarian crisis. Science and technology do provide comfort and happiness, but on the other hand, they bring about a multidimensional crisis, which leads to a process of alienation, lack of spirituality and drought in the meaning of essential life for humans and their environment. So that humans experience the moral degradation of life and social ethics decadence in the realm of humanity. This modernity civilization awakens humanity to return to a past civilization that is full of divine values to humanize humans. So among Muslim scientists, there is an awareness to reconstruct science and Islamization of knowledge. The Islamization discourse of knowledge is an idea to reinvent modern science based on religion and monotheism. The Islamization of knowledge, through a process of approaches and efforts towards the convergence of Islamic knowledge which is included in it puts forward aspects of value, revelation and nature Keywords: Islamization of Knowledge, Convergence, Islamic Civilization Abstrak Perkembangan dan kemajuan ilmu pengetahuan dan teknologi memunculkan peradaban modern yang memberikan manfaat dan kemudahan bagi manusia, namun dalam realitasnya membawa implikasi negatif pada krisis kemanusiaan global kini. Ilmu pengetahuan dan teknologi memang memberi kenyamanan dan kebahagiaan, namun di sisi lain membawa krisis multidimensi, yang membawa manusia pada proses alienasi, minimnya spiritualitas dan kekeringan akan makna hidup hakiki bagi manusia dengan lingkungannya. Sehingga manusia mengalami degradasi moral kehidupan dan dekadensi etika social pada ranah kemanusiaannya. Peradaban modernitas ini menyadarkan umat manusia untuk kembali kepada peradaban lampau yang penuh nilai-nilai ilahiyah memanusiakan manusia. Maka di kalangan ilmuwan muslim muncul kesadaran untuk melakukan rekonstruksi ilmu pengetahuan dan Islamisasi sains. Wacana Islamisasi pengetahuan merupakan ide untuk menemukan kembali ilmu pengetahuan modern yang berbasiskan religius dan monoteisme. Islamisasi ilmu pengetahuan, melalui proses pendekatan dan usaha terhadap konvergensi ilmu pengetahuan Islami yang included didalamnya mengedepankan aspek nilai, wahyu dan alam Kata Kunci: Islamisasi Ilmu Pengetahuan, Konvergensi, Peradaban Islam